The Influence of Motivation and Self Concept on English Achievement of Tenth Grade at MA Negeri Sidenreng Rappang - Hamka, Hudzaifa Afifah; Jabu, Baso; Halim, Abd. (Journal of Excellence in English Language Education, 2024)
The objectives of the researcher were to investigate whether motivation has a significant influence on the students’ achievement and to investigate does self-concept has a significant influence on the students’ achievement. This research took place at MA Negeri Sidenreng Rappang. The tenth grade of MA Negeri Sidenreng Rappang was chosen as the population of the research. This research used systematic random sampling in selecting the sample. This method of this research was descriptive quantitative research. The instrument of this research used questionnaires for the students and students’ scores in English achievement. The data were analyzed by using the Likert scale and descriptive statistics through the SPSS 25 version. Based on the result of SPSS analysis the influence of motivation (X1) and English achievement (Y) was positive and significant with sig. 0.009 < 0.05 and (t count 2.813) > (t table 2.052). The result of SPSS analysis about the influence of self-concept (X2) and English learning achievement (Y) was positive and significant with sig. 0.009 < 0.05 and (t count 2.798) > (t table 2.052). This means that motivation and self-concept have an influence on English achievement.